Efisiensi Penggunaan Grey Water dan Air Hujan dalam Rangka Menurunkan Tingkat Penggunaan Air Baku - Hidayat, Muhamad Yusup; Fauzi, Ridwan; Harianja, Alfonsus Hasudungan; Saragih, Grace Serepina (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTThe population growth rate in big cities such as Jakarta and its satellite cities has a correlation that is directly proportional to the level of clean water consumption. The biggest consumption of clean water is generally used for domestic household needs. However, the use of clean water is still not efficient. Therefore, the efficiency of water-saving needs to be carried out by utilizing sources that have not been optimally used, for example, greywater and rainwater. The purpose of this study is to determine the level of water usage in 3 (three) types of housing and the level of efficiency of utilization of domestic wastewater (greywater) and rainfall (CH) in reducing the use of clean water. This research was performed in the Villa Bintang Mas residential area in the City of South Tangerang, the Villa Bintang Mas residential area in the City of Depok, and the Selakopi Hijau/Forestry residential area in the City of Bogor. Data collection was conducted by a series of surveys using a questionnaire on the sample of a household. The results show that the data processing needs of clean water in three residentials range of values between Ã‚Â± 158.84 Liters/person/day up to Ã‚Â± 215.38 Liters/person/day. The level of efficiency of the utilization of greywater and rainwater in reducing the usage of clean water in three housing ranges from 21.12% to 58.47%.Keywords: Domestic Waste, the Use of Clean WaterÃ‚Â ABSTRAKTingkat pertumbuhan penduduk diÃ‚Â kota-kota besar seperti jakarta dan kota-kota satelitnya memiliki korelasi yang berbanding lurus dengan tingkat konsumsi air bersih yang dimanfaatkan oleh masyarakat. Konsumsi air bersih terbesar adalah untuk kebutuhan domestik rumah tangga. Penggunaan air bersih saat ini masih belum mengikuti kaidah efisiensi dalam penggunaannya, untuk itu efisiensi penghematanÃ‚Â air perlu segera dilakukan dengan memanfaatkanÃ‚Â sumber-sumber lain yang belum termanfaatkan, antara lain air limbah domestik rumah tangga (grey water) dan air hujan. Tujuan dari penelitian ini adalah mengetahui tingkat pemakaian air di 3 (tiga) tipe perumahan,serta tingkat efisiensi pemanfaatan air limbah domestik rumah tangga (grey water) serta curah hujan (CH) dalam menurunkan pemakaian air bersih. Penelitian ini dilaksanakan di Perumahan Villa Bintang Mas, Kota Tangerang Selatan, Perumahan Permata Depok, Kota Depok, dan Perumahan Selakopi Hijau/Kehutanan, Kota Bogor. Pengambilan data dilakukan dengan cara survei menggunakan kuesioner pada rumah tangga yang menjadi sampel. Hasil pengolahan data memperlihatkan bahwa kebutuhan air bersih di tiga perumahan berkisar pada rentang nilai antara Ã‚Â±158,84 Liter/Orang/Hari sampai dengan Ã‚Â± 215.38 Liter/Orang/Hari. Tingkat efisiensi pemanfaatan grey water dan air hujan dalam mengurangi pemakaian air bersih di tiga perumahan berkisar antara 21,12%Ã‚Â hingga 58,47%.Kata kunci: Limbah Domestik, Penggunaan Air BersihÃ‚Â